2021
DOI: 10.5817/cp2021-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Are online behaviors damaging our in-person connections? Passive versus active social media use on romantic relationships

Abstract: Social media has been extensively researched, and its impact on well-being is becoming more clear. What is less clear, however, is the role of social media on romantic relationships, with the few existing studies finding mixed results. In an attempt to reconcile these discrepancies, the current study explored types of social media use (i.e., active use and passive use) as moderators between frequency of social media use and relationship health (i.e., relationship satisfaction and commitment). Participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
1
10
0
3
Order By: Relevance
“…This consideration was subsequently nuanced, as mixed evidence has emerged; that is, the use of SM is beneficial when employed to create meaningful social connections, but harmful in situations such as isolation and social comparison (Clark et al, 2018). Although SM are designed to promote social connection and interaction, many SM users engage in passive utilization, rarely interacting with others' content (Quiroz & Mickelson, 2021). Thus, among passive SM users -though not limited to them-no interpersonal connections are generated, fostering conditions of isolation and social comparison, which influence personal well-being (Clark et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This consideration was subsequently nuanced, as mixed evidence has emerged; that is, the use of SM is beneficial when employed to create meaningful social connections, but harmful in situations such as isolation and social comparison (Clark et al, 2018). Although SM are designed to promote social connection and interaction, many SM users engage in passive utilization, rarely interacting with others' content (Quiroz & Mickelson, 2021). Thus, among passive SM users -though not limited to them-no interpersonal connections are generated, fostering conditions of isolation and social comparison, which influence personal well-being (Clark et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(Lenne et al, 2019). In a further study, women with low social comparison orientation are found to show a negative relationship between usage of SNS and relationship satisfaction, and for men, higher social comparison orientation was associated with lower commitment (Quiroz, 2019). In addition to these findings, in a study dealing with the effect of attachment patterns, which is one of the personal factors, only the effect of anxious attachment pattern was found to be significant in the relationship comparison performed on the SNS.…”
Section: Relationship Social Comparisonsmentioning
confidence: 77%
“…This may be explained by the fact that, due to the lockdown, billions of people were forced to work and to study from home. As a consequence, their need of socializing leads to an amplified interest in social networking and an increased frequency and duration of social media usage (Quiroz and Mickelson, 2021). The influencers’ now have a huge impact on the consumer’s decision-making.…”
Section: Resultsmentioning
confidence: 99%